2002
DOI: 10.1002/cncr.10827
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in treatment and survival from early‐stage breast carcinoma

Abstract: BACKGROUNDAfrican‐American women have a significantly worse prognosis from breast carcinoma compared with white women, even when the stage at diagnosis is equivalent. The purpose of this study was to analyze racial differences in the treatment (use of breast‐conserving surgery and radiation therapy) of women with early‐stage breast carcinoma and the resulting effects on survival rates.METHODSSubjects included 10,073 African‐American and 123,127 white women diagnosed with Stage I, IIA, or IIB breast carcinoma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 49 publications
7
80
1
Order By: Relevance
“…10 Moreover, other nonrandomized studies have demonstrated similar findings. 18,20 The results from our population-based study are consistent with the ECTCG study. Indeed, our study indicated that increased mortality rates with the omission of RT were observed for all patients regardless of ER status.…”
Section: Discussionsupporting
confidence: 87%
“…10 Moreover, other nonrandomized studies have demonstrated similar findings. 18,20 The results from our population-based study are consistent with the ECTCG study. Indeed, our study indicated that increased mortality rates with the omission of RT were observed for all patients regardless of ER status.…”
Section: Discussionsupporting
confidence: 87%
“…3,[5][6][7] Low rates of cancer treatment appointment keeping, lower rates of receipt of adjuvant therapy, and early treatment termination have been described. 3,[8][9][10][11][12][13][14][15][16][17][18] However, these studies largely focus on black and Hispanic minority populations, with few authors examining disparities in treatment and survival among Asians. There are no studies assessing cancer treatment appointment keeping among Chinese immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, racial disparities have been documented in rates of surgical resection for breast, esophageal, colorectal, and non-small-cell lung cancer (NSCLC) [1][2][3][4][5]. There are also disparities in the postoperative management of patients, with lower rates of radiation therapy among some demographic groups after breast-conserving surgery (BCS) or resection for rectal cancer [3,6]. Socioeconomic status (SES) has been shown to influence surgical decision making, with lower SES associated with lower rates of BCS and postmastectomy reconstruction for breast cancer, less sphincter-sparing surgery for rectal cancer, and lower rates of staging procedures for NSCLC [2,3,[7][8][9][10][11].…”
mentioning
confidence: 99%